Development of a Hand-Held near Infrared System Based on an Android OS and MicroNIR, and its Application in Measuring Soluble Solids Content in Fuji Apples. Issue 4 (June 2014) - Yan, Hui; Lu, Dao-Li; Chen, Bin; Hansen, Wei G.
Near infrared (NIR) spectroscopy has been widely applied in the areas of agriculture, food, pharmaceutical and chemical industries because of its advantages such as its speed, non-destructive nature and simultaneous detection of multiple components. However, most existing NIR instruments are too large to be carried into the field. Herein, we have developed an interface by which the application (app) runs on a smart phone (or tablet) to drive a miniature NIR spectrometer (MicroNIR, a product of the JDSU Uniphase Corporation). This app has three modules; the first drives the hardware to control the spectrometer; the second facilitates graphical display of spectral data, spectral pretreatment according to method provided by the model file and production of a calculated result while the third is the management of models, samples, spectral parameter setting and an address book. We have used this app with the MicroNIR to measure soluble solids content (SSC) in Fuji apples in the field; results were compatible with the reference results based on an Abbé refractometer analysis. To conclude, this new hand-held NIR spectroscopy system based on android device is convenient and practical in rapid measurement of SSC of Fuji apples in the field. It has potential to be used for in situ measurement of other constituents of agriculture products.